PENGARUH LITERASI KEUANGAN, PENDAPATAN DAN GAYA HIDUP TERHADAP KEPUTUSAN INVESTASI EMAS DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERASI - Irma Chairani Tambunan; Andri Soemitra (Jurnal Akuntansi dan Pajak, 2023)
Indonesia has entered the era of globalization where the increase and growth of investment in countries around the world, including Indonesia, has had an impact on the financial behavior of the Indonesian people in meeting their needs. More money over time, let alone using that money to invest. This study aims to examine and analyze the effect of variables, financial literacy, income and lifestyle on gold investment decisions with thecutus of control as a moderating variable at BSI KCP Medan P. Bulan for 2019 – 2021. The population in this study are gold investors at BSI KCP Medan P. Bulan. obtained a sample of 607 investors, then the sample that will meet the characteristics has been made on the slovin formula and the margin of error is set at 10%, so the total sample is 86 investors. The analysis technique used is a measurement model and a structural model. The statistical method used for this research is Structural Equation Modeling (SEM) which is operated through the SmartPLS program. The conclusions of the research results show that: (1) financial literacy has a significant positive effect on gold investment decisions, (2) income has no significant positive effect on gold investment decisions, (3) lifestyle has no significant positive effect on gold investment decisions, (4) locus of control cannot moderate financial literacy, (5) locus of control is able to moderate income, (6) locus of control cannot moderate lifestyle, (7) locus of control has a significant positive effect on gold investment decisions.